Broad‐Band Time‐Resolved Near Infrared Spectroscopy in the TJ‐II Stellarator. Issue 10 (November 2014) - Rodriguez, M. C.; Pastor, I.; de la Cal, E.; McCarthy, K. J.; Diaz, D.
Abstract First experimental results on broad‐band, time‐resolved Near Infrared (NIR;here loosely defined as covering from 750 to 1650 nm) passive spectroscopy using a high sensitivity InGaAs detector are reported for the TJ‐II Stellarator. Experimental set‐up is described together with its main characteristics, the most remarkable ones being its enhanced NIR response, broadband spectrum acquisition in a single shot, and time‐resolved measurements with up to 1.8 kHz spectral rate. Prospects for future work and more extended physics studies in this newly open spectral region in TJ‐II are discussed. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)